2013
DOI: 10.3126/mjsbh.v12i1.9093
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Anomaly in Circle of Willis

Abstract: Anomalies in circle of Willis are very common and complete functioning ring as classically described is found only in 85 % of population. Most anomalies however are in posterior segment. We report a case of rare anomaly of anterior segment, where anterior communicating artery was completely absent and both anterior cerebral arteries arose from right internal carotid artery. Since both the frontal lobes of cerebrum are dependent upon right internal carotid artery for vascularization, with a poor communication w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…As for the descriptions of the origin of the left and right ACAs from one ICA, as described by Burbank and Morris [5], and Kawaji et al [23], a persistent POℓA probably assumed the role of the "second" ACA [32,33,52]. Similar descriptions were also found in the articles of Pokhrel and Bhatnagar [40], and Saikia et al [43], but their schema and/or images do not correspond to the text, i.e. these images presented bihemispheric ACAs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As for the descriptions of the origin of the left and right ACAs from one ICA, as described by Burbank and Morris [5], and Kawaji et al [23], a persistent POℓA probably assumed the role of the "second" ACA [32,33,52]. Similar descriptions were also found in the articles of Pokhrel and Bhatnagar [40], and Saikia et al [43], but their schema and/or images do not correspond to the text, i.e. these images presented bihemispheric ACAs.…”
Section: Discussionmentioning
confidence: 52%
“…It distributes anteromedial central branches in the A1 part; the proximal medial striate arteries from the previous group of branches supply the anterior hypothalamus, the septum pellucidum, the anterior cerebral commissure, the fornix and the striatum, while the preoptic, supraoptic and the anterior perforating arteries, also from the previous group of branches, supply the corresponding nuclei of diencephalon [9]. However, there were descriptions of many morphologic variations of the ACA, such as the origin of both of the ACAs from one ICA [5,23,40], or A1 aplasia [4,10,15,27,29,37], or hypoplasia [1,8,17,22,27,28,44,49,51,52], or an unusual course [23,36,42], or distibution of variable branches [26,38,51], or a fenestration [11,13,20,38,49,53], or a nonunion with the opposite ACA [38,51], or forming of the so-called azygos pericallosal artery [11,38,47,50], or tripling of the A2 parts [1,11,47,50]. Many authors found an association between pathologic disorders and ACA variations [19,24,…”
Section: Introductionmentioning
confidence: 99%